Pengaruh Total Quality Management terhadap Kinerja Manajerial: (Studi Empiris pada Bank BRI) - Fitria, Fitria (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
The era of globalization reach out to various aspects of life. Business organization first compete on a local level & national only. Where the moment is all companies competing around the world, therefore the company must make improvements continuously. By using TQM we can improve the quality of the company. Here we will look at the influence of managerial performance against TQM. TQM Does by manufactory companies while banking is still less that apply. In this research show that TQM and the performance at the production Management has significant influence. The research we conducted at BRI where located in Payakumbuh, Padang and Bukittinggi. 0.0 where smaller than 0.05 means there are influences between variabel.